UPAYA PENINGKATAN HASIL BELAJAR MAHASISWA DALAM PEMBELAJARAN ATLETIK LARI 100 M MELALUI PEMANASAN MENGGUNAKAN PERMAINAN OLAHRAGA TRADISIONAL BENTENGAN - Rahmat, Ayi; Aryadi, Dedi (Jurnal Pendidikan Dasar Setiabudhi, 2019)
Inadequate learning methods as well as inadequate learning process in the 100 m running athletic learning process result in student learning outcomes that are not optimal. The problem problem in research is "Does warming up with traditional sports games can increase the athletic learning outcomes of Running 100 m in STKIP Setia Budhi students. To find out the quality of student learning outcomes in following the lecture process is indicated by the results of performance tests. This research uses the action research method. The object of research using the method of warming up traditional sports games with the subject of research is STKIP students. The sample used was 24 students. The instrument used in data retrieval was obtained from the results of performance tests demonstrated by students during the implementation of the test. From the results of research conducted, an increase in student learning outcomes from pre-cycle conditions to cycle I and cycle II, both from an increase in the average value of 100 m running athletics and the value of completeness of learning outcomes. The average value of pre-cycle (65.29), the average value of cycle I (67.46), increased by (2.17) from pre-cycle to cycle I, and the average value of cycle II (72.21), experienced an increase of (4.75) from cycle I to cycle II. Improvement of the ability of movement in learning athletics running 100 m can be seen from the KKM value (7.00), after taking action in the first cycle the value of students' learning complete as many as 14 of 24 students (58.33%) and in the second cycle which has a value in on KKM as many as 17 out of 24 students in total or complete (70.83%). The conclusion of this research is the use of the warm-up method using traditional sports games to improve the learning outcomes of 100m running athletics for Physical Education Study Program students. The suggestion in this study is the use of more innovative learning methods that can increase student interest and motivation in following the lecture process so that it influences towards increasing optimal learning outcomes. Keywords: Action Research, Warming Method with games, Athletic Sports. Abstrak Metode pembelajaran yang kurang tepat serta proses pembelajaran yang kurang memadai dalam proses pembelajaran atletik lari 100 m mengakibatkan hasil belajar siswa tidak optimal. Rumusan masalah dalam penelitian adalah “Apakah dengan pemanasan permainan olahraga tradisional bentengan dapat meningkatkan hasil belajar atletik Lari 100 m pada mahasiswa STKIP Setia Budhi. Untuk mengetahui kualitas hasil belajar mahasiswa dalam mengikuti proses perkuliahan ditunjukkan dengan hasil tes unjuk kerja. Penelitian ini menggunakan metode penelitian tindakan. Objek penelitian menggunakan metode pemanasan permainan olahraga tradisional bentengan subjek penelitiannya adalah mahasiswa STKIP. Sampel yang digunakan adalah 24 mahasiswa. Instrumen yang digunakan dalam pengambilan data diperoleh dari hasil tes unjuk kerja yang didemonstrasikan siswa saat pelaksanaan tes. Dari hasil penelitian yang dilakukan, terjadi peningkatan hasil belajar mahasiswa dari kondisi prasiklus ke siklus I dan siklus II, baik dari peningkatan nilai rata-rata pembelajaran atletik lari 100 m maupun nilai ketuntasan hasil belajaran. Nilai rata-rata prasiklus (65,29), nilai rata-rata siklus I (67,46), mengalami peningkatan sebanyak (2,17) dari prasiklus ke siklus I, dan nilai rata-rata siklus II (72,21), mengalami peningkatan sebanyak (4,75) dari siklus I ke siklus II. Peningkatan kemampuan gerak pada pembelajaran atletik lari 100 m dapat dilihat dari nilai KKM (7,00), setelah dilakukan tindakan pada siklus I nilai belajar siswa yang tuntas sebanyak 14 dari 24 Mahasiswa (58,33%) dan pada siklus II yang memiliki nilai di atas KKM sebanyak 17 dari 24 Mahasiswa keseluruhan atau tuntas sebesar (70,83%). Kesimpulan peneliti ini adalah penggunaan metode pemanasan menggunakan permainan olahraga tradisional bentengan meningkatkan hasil belajar atletik lari 100 m pada mahasiswa Prodi Penjas. Saran dalam penelitian ini adalah penggunaan metode pembelajaran yang lebih inovatif dapat meningkatkan minat dan motivasi mahasiswa dalam mengikuti proses Perkuliahan sehingga berpengaruh terhadap peningkatan hasil belajar yang optimal. Kata kunci : Penelitian Tindakan, Metode Pemanasan dengan permainan, Olahraga Atletik.